Deer mandible tools: an examination of Oneota modified mandibles from La Crosse County, Wisconsin - Lager, Michael Wagner (My University, 2010)
This study focuses on the modified deer mandibles that have been recovered at late prehistoric Oneota sites over the last few decades by the M.V.A.C. in La Crosse County, Wisconsin. The purpose of this study is to clarify through experimentation the function of Oneota tools made from deer mandibles. Of the numerous deer mandibles and deer mandible fragments that have been recovered from Oneota context in the La Crosse locality there are a set of five deer mandibles, which show signs of heavy wear along the fracture of the bone marrow cavity where they were broken, presumably to obtain the marrow. These artifacts were found at the Pammel Creek site (47Lc61), the Valley View site (47Lc34), and the Gundersen Lutheran site (47Lc394), and the Sand Lake site (47Lc44). Experimental use demonstrated that the Oneota mandibles were identified as hide scrapers, which were used to soften leather for hide working.
Keywords: Deer -- Wisconsin -- La Crosse County -- Anatomy.; Deer -- Wisconsin -- La Crosse County -- Morphology.; Mammal populations -- Wisconsin -- La Crosse County.